Connection Of Heavy Metals (Pb, Hg, Cd) In Raw Water In Gasami Fisheries (Osphronemus Gouramy) At Pandaan Pasuruan Freshwater Management Unit - muhammad tri aji (Universitas Tidar, 2018)
The raw water is the main water used as a medium carp hatchery process performed by the unit Pengelolah freshwater aquaculture (UPBAT) Pandaan conducted, in this case the raw water is derived from well water and river water. In order to make the program successful that CPIB Central Government digalahkan, this water must be considered and examined since water is the main medium in the vaccination process, and also water is also very susceptible to pollution. But the facts on the ground show that there are still many farmers who are still underestimated and do not pay attention to the heavy metal content in the raw water in the vaccination process of carp. Based on this study, it is necessary to determine the content of heavy metals lead (Pb), mercury (Hg), cadmium (Cd) in raw water for carp fish farming (Osphronemus gouramy). Data recovery method uses appropriate samples. Water samples were taken from 2 different points and analyzed using the AAS method (Atomic Absorption Spectrophotometry). The results of the measurement of heavy metals Pb, Hg and Cd, showing the difference between river water and well water. The content of heavy metals from river water and well water is Pb or 0.0031 mg / l - 0.0033 mg / l and 0.0001 mg / l; 0.0011 mg / L -0.0012 mg / L and 0.00071 mg / L-0.00072 mg / L; Cd 0.0052 mg / l -0.0054 mg / l and 0.0012 mg / l -0.0013 mg / l. And the water source still does not exceed government quality standards.